Pelatihan Manajemen Keuangan Bagi Pelaku Home Industry Pupuk Organik Di Desa Kopeng - Hendrayanti, Silvia; Wanuri, Wanuri; Sundari, Pipit (Jurnal Abdimas Ekonomi dan Bisnis, 2024)
The growth of the home industry producing organic fertilizer in Kopeng Village is starting to grow. The large number of organic fertilizer businesses emerging has increasingly added to the competition in Kopeng Village. Home industry players must also be able to maintain the characteristics and quality so that they can produce quality and attractive organic fertilizer. However, in the midst of the development of the organic fertilizer home industry, various obstacles are often faced by home industry players, namely capital problems and poor financial management, making it difficult for business people to obtain credit/capital from banks. Realizing this, the PKM Team carried out service with the aim of providing knowledge and helping manage finances for home industry business actors as a result of the fairly high competition in the business world. In this service, PKM participants are given training in determining selling prices, making purchase and sales reports, as well as helping to calculate the desired profit and conducting training in preparing simple financial reports. The methods used in this service activity are observation, presentation of material and training practices regarding good financial management. The target audience for this service activity is home industry business actors in Kopeng Village and who are members of the Memayu Jogo Tonggo Kopeng cooperative, totaling 10 organic fertilizer home industry businesses. From the pre-test results, only 20% of participants had knowledge about financial management, while the other 80% of participants had no knowledge at all about financial management. Likewise with knowledge of financial reports and knowledge of general journals. From the post test results, it shows an increase in the participants' abilities and knowledge. The most significant increase was knowledge about financial management which provided an increase of up to 100% because the material provider succeeded in providing exposure and practicum in preparing simple financial reports directly for home industry business actors producing organic fertilizer.